Essays in identifying demand-led growth regimes - Carrillo Maldonado, Paul Alexander (2022)
This study presents two different and novel methodologies to evaluate the effects of changes in the functional distribution of income on economic activity and identify the regime of growth of an economy. This study problem goes back to the works of classical economists, but that has been renewed within the modern theories of growth developed by the post-Keynesian school of thought. The basic logic of the relationship between income distribution and aggregate demand has been widely developed in the so-called neo-Kaleckian macro models giving rise to the possibility of identifying growth regimes. The main distinction (though not the only one) is between profit-led and wage-led growth regimes.